Recent advances in the biocontrol of Xanthomonas spp. - Marin, Vítor Rodrigues [UNESP]; Ferrarezi, Juliano Henrique [UNESP]; Vieira, Gabrielle [UNESP]; Sass, Daiane Cristina [UNESP] (Springer Nature, 2019)
Bacterial diseases caused by members of the genus Xanthomonas affect agricultural crops of great importance in the world. At least 350 different plant diseases are caused by species of Xanthomonas. Important crops, such as: rice, citrus, cassava, tomato, sugar cane, passionfruit and brassicas are severely affected by bacteria of this genus. Due to its rapid propagation, handling difficulties, problems with chemical control and severity of the losses of the affected plantations Xanthomonas is a difficult obstacle for agriculture around the world. In addition, chemical control of some of these diseases is carried out using copper-based chemicals, which causes a negative impact on health and the environment. A more sustainable alternative to combat these diseases is the control of Xanthomonas by microorganisms directly or indirectly through the use of its secondary metabolites involved in biocontrol. This review is a report concerning the recent advances in the search for microorganisms for the biocontrol of several Xanthomonas that are important for the world economy.
Keywords: Agriculture; Biocontrol; Phytopathogens; Xanthomonas